2019
DOI: 10.1038/s41590-019-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 receptor–based signaling and implications for disease

Abstract: Interleukin 17 (IL-17) is a highly versatile pro-inflammatory cytokine crucial for a variety of processes including host defense, tissue repair, inflammatory disease pathogenesis and cancer progression. In contrast to its profound impact in vivo, IL-17 exhibits surprisingly moderate activity in cell culture models, presenting a major knowledge gap regarding the molecular mechanisms of IL-17 signaling. Emerging studies reveal a new dimension of complexity in the IL-17 pathway that may help explain its potent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
281
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(312 citation statements)
references
References 154 publications
2
281
1
Order By: Relevance
“…Despite we found an increase of several components of the IL17 signaling (IL17RA, TRAF6, TYK2) and its downstream effectors CEBPD and CEBPB in both MM and MGUS HDNs, we did not test in vitro the effect of IL17 on neutrophils function, because of lack of ILR17C, required for the full receptor assembly to work properly 81,82 . We also found that IL17RD is higher in MM-than MGUS-HDNs, but its ligand is still unknown 82 ; it is questionable if it could be involved in the STAT3 activation exerted by soluble mediators released by the MMconditioned media. On the other hand, the paracrine effects of IL17 can be due to the gram-negative microbiome composition, able to affect the evolution from MGUS to MM, as recently shown in Vk*MYC mice 83 .…”
Section: Discussionmentioning
confidence: 83%
“…Despite we found an increase of several components of the IL17 signaling (IL17RA, TRAF6, TYK2) and its downstream effectors CEBPD and CEBPB in both MM and MGUS HDNs, we did not test in vitro the effect of IL17 on neutrophils function, because of lack of ILR17C, required for the full receptor assembly to work properly 81,82 . We also found that IL17RD is higher in MM-than MGUS-HDNs, but its ligand is still unknown 82 ; it is questionable if it could be involved in the STAT3 activation exerted by soluble mediators released by the MMconditioned media. On the other hand, the paracrine effects of IL17 can be due to the gram-negative microbiome composition, able to affect the evolution from MGUS to MM, as recently shown in Vk*MYC mice 83 .…”
Section: Discussionmentioning
confidence: 83%
“…Chemokines such as CXCL1, CXCL2, CXCL5 have chemotactic activity in neutrophils, they play role in inflammation and target injured or infected tissues (Li et al, 2019).…”
Section: Il-17 Signalling Pathwaymentioning
confidence: 99%
“…Binding of dimeric IL-17 leads to heterodimerization of the receptor (Ely et al, 2009;Liu et al, 2013;Goepfert et al, 2017) and recruitment of a cytoplasmic protein ACT1 (Chang et al, 2006;Qian et al, 2007). ACT1 was described to enhance the expression of genes encoding proinflammatory cytokines by stabilizing their mRNAs or by activating downstream signaling pathways leading to the activation of their transcription (Li et al, 2019). The gene-activation pathways are dependent on the recruitment of E3 ubiquitin ligases from tumor necrosis factor (TNF) receptor-associated factors (TRAFs) family, most prominently TRAF6.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms promoting and regulating IL-17 signaling emanating directly from IL-17 receptor are incompletely understood. The IL-17-induced activation of downstream pathways is surprisingly weak in comparison with other proinflammatory cytokines such as IL-1a or TNF, although their receptors all employ the formation of non-degradative polyubiquitin linkages and share multiple proximal signaling proteins (Kupka et al, 2016;Strickson et al, 2017;Li et al, 2019;McGeachy et al, 2019). The molecular basis for these differences is poorly defined.…”
Section: Introductionmentioning
confidence: 99%